KETERKAITAN PENDIDIKAN DAN PERENCANAAN KEHAMILAN DENGAN KELENGKAPAN PELAYANAN ANTENATAL DI WILAYAH KERJAÂ PUSKESMAS KABUPATEN MOJOKERTO - Meilinawati SB, Elies; Roifah, Ifa (JURNAL KEPERAWATAN BINA SEHAT, 2013)
Antenatal care aims to prevent and treat conditions that can threaten the health of the fetus / new born baby and or mother. Indicators of access monitoring coverage of antenatal care use K1, service indicator pregnant women with K4 scope. K1 and K4 coverage gap in the region indicate that there are still women who are not pregnant monitored by default, if the dropout rate K1 - K4 more than 10 % means that the region is problematic and needs to search. The purpose of this study was to analyze the relationship between education and pregnancy planning with complete antenatal care in women in Mojokerto regency.The study design was cross sectional. The number of respondents was 140 K1 ever recorded in 2011. Data were analyzed with bivariate and multivariable chi square test and multiple logistic regression. The results of this study are in bivariate relationship exists between education (p = 0.001) and planning a pregnancy (p < 0.001) with complete antenatal care , the results obtained in multi- variable education ( p = 0.012 , POR = 3.299 , IK95 % = 1.307 to 8.327 ) and planning a pregnancy ( p < 0.001 , POR = 8.817 , IK95 % = 3.843 to 20.233).The conclusions of this study are mothers with secondary education up and have a mother who is planning a pregnancy completeness of antenatal care compared to mothers with primary education and women with unplanned pregnancies .Keywords : antenatal care , education , planning a pregnancy